Metode Penilaian Walkability Permukiman di Perkotaan: Sebuah Kajian Literatur Sistematis - Sondakh, Alva F.P. (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2017)
Neighborhood Walkability is an important factor in urban life. The purpose of this systematic review is to identify the variables used in the measurements, to identify the methods of data collection, to identify the research instruments, and to identify the methods of data analysis used by previous researchs on Neighborhood Walkability. This review used a systematic literature review method on 19 articles about Neighborhood Walkability. Results of analysis and interpretation has shown that a combination of measuring factual condition and perceptual opinion is best to describe the Neighborhood Walkability.Keywords: assesment method, neighborhood walkability, neighborhood accessibility, urban quality of life.